Knowledge and attitude on prevention of COVID-19 among community health workers in Nepal-a cross-sectional study - Amul Shrestha; Tek Bahadur Thapa; Mahendra Giri; Sanjiv Kumar; Sakil Dhobi; Haikali Thapa; Pawan Prakash Dhami; Arun Shahi; Ajita Ghimire; Ela Singh Rathaur (BMC, 2021)
Abstract Background Emerging and reemerging pathogens are global challenges for public health and the pandemic of Coronavirus disease 2019is a reemerging case of an infectious disease caused by Severe Acute Respiratory Syndrome-Corornavirus-2. Health care worker worldwide are at higher risk worldwide and the situation is the same in Nepal. The knowledge and attitude of health workers will certainly mark the outcome towards this pandemic. So, this study aims to assess the knowledge and attitude of community health workers towards the prevention of COVID-19 virus. Methods A descriptive cross-sectional study was carried out among the community health workers of various provinces of Nepal. A semi-structured, self-administered questionnaire was prepared in Google form and circulated to the sampled health workers through various social media platforms like face book, messenger, Instagram and g-mails. A total of 650 invitations were send and among them 420 responded and among them only 399 provided complete response. Responses containing anonymized data was collected analyzed in using SPSS-version-20. The results were interpreted and was checked with various demographic and enabling factors using chi-square test and logistic regression model. Also, ethical approval was taken from NHRC (Nepal Health Research Council (protocol registration number: 360/2020P) prior to the conduction of study. Results Out the total sample size of 450, we took 399 responses taking into consideration all the inclusion criteria. So, from 399 valid response, 230 (47.6%) were males and 169 (42.4%) were females. 380 (95.2%) employed participants thought that wearing PPE will reduce the chances of getting COVID-19, majority of the participants 80.5% (321) responded that COVID-19 will successfully be controlled and staffs receiving excellent support from palika had high knowledge level. Knowledge level was significantly associated with the enabling factor "support from palika" (P = 0.045).45.9% of the respondents had no availability of COVID-19 response medical items for prevention of COVID-19 at their respective health facilities. Also the logistic regression analysis revealed that the odds of knowledge level was 2 times higher (AOR=1.913 at 95% CI: 1.266-2.891) compared to the female participants (Ref- female). Conclusions Proper and adequate knowledge and attitude towards COVID-19 is a paramount in the prevention and control of SARS-COV-2. Health care workers are knowledgeable about COVID-19 and are proactively practicing the preventive measures to minimize the spread of infection but some lack optimistic attitude. Hence, the constantly updated educational programs related to COVID-19 will surely contribute to improving the healthcare workers knowledge and attitude towards COVID-19.